2021
DOI: 10.3390/antiox10020182
|View full text |Cite
|
Sign up to set email alerts
|

Phytogenic Fabrication of Ag–Fe Bimetallic Nanoparticles for Cell Cycle Arrest and Apoptosis Signaling Pathways in Candida auris by Generating Oxidative Stress

Abstract: Novel green synthetic nanomedicines have been recognized as alternative therapies with the potential to be antifungal agents. Apoptosis induction, cell cycle arrest and activation of the antioxidant defense system in fungal cells have also gained attention as emerging drug targets. In this study, a facile and biodegradable synthetic route was developed to prepare Ag–Fe bimetallic nanoparticles using aqueous extract of Beta vulgaris L. Surface plasmon resonance of Beta vulgaris-assisted AgNPs nanoparticles was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 91 publications
3
15
0
Order By: Relevance
“…The biogenic synthesis of Ag-Ni nanoparticles was initially confirmed by UV-visible spectrophotometry by recording the absorbance of the Salvia officinalis aqueous extract, silver nanoparticles (Ag NPs), nickel nanoparticles (Ni NPs), and Ag-Ni nanoparticles in the wavelength range of 200–800 nm. The Salvia officinalis aqueous extract shows an absorption peak at 325 nm that could be due to the π-π transition [ 59 ], which signifies the presence of polyphenolic compounds present in the Salvia officinalis aqueous extract ( Figure 2 a). The absorption band of Salvia officinalis extract disappears in synthesized Ni NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The biogenic synthesis of Ag-Ni nanoparticles was initially confirmed by UV-visible spectrophotometry by recording the absorbance of the Salvia officinalis aqueous extract, silver nanoparticles (Ag NPs), nickel nanoparticles (Ni NPs), and Ag-Ni nanoparticles in the wavelength range of 200–800 nm. The Salvia officinalis aqueous extract shows an absorption peak at 325 nm that could be due to the π-π transition [ 59 ], which signifies the presence of polyphenolic compounds present in the Salvia officinalis aqueous extract ( Figure 2 a). The absorption band of Salvia officinalis extract disappears in synthesized Ni NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The antifungal properties of bio-fabricated ZnONPs make ZnONPs a good candidate for bioactive food packaging materials. In our previous studies, we have reported antifungal activity and induction of apoptosis in C. auris using biogenic metallic nanoparticles [ 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Ag@FeHCF a peak at 608 cm À1 was not found in the FeHCF complex, but it was present in Ag-Fe nanoparticles, so the bond between Ag-Fe was confirmed. 45 Ag@ZnHCF contains a peak at 762 cm À1 which was not present in pure ZnHCF but this was present in Ag-Zn nanoparticles nearby 680 cm À146 This will confirm a bond in between Zn and Ag shown in Figure 2.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 68%